23-level Single DC Source Hybrid PUC (H-PUC) Converter Topology With Reduced Number of Components: Real-Time Implementation With Model Predictive Control - Sorto-Ventura, Kevin-Rafael; Abarzadeh, Mostafa; Al-Haddad, Kamal; Dessaint, Louis A. (IEEE open journal of the Industrial Electronics Society, 2020)
In this paper, a new configuration of single DC source hybrid packed U-cell (H-PUC) converter with reduced number of components is proposed. The proposed H-PUC only requires one dc source, twelve power switches, and three capacitors to provide 23-level output voltage. It is comprised of two high voltage low frequency (LF) and low voltage high frequency (HF) sub-modules which leads to less power losses and higher efficiency of the proposed H-PUC converter. Moreover, a finite control set model predictive control (FCS-MPC) method is proposed to generate 23-level staircase output voltage with low THD and to regulate voltages of three capacitors to their desired values simultaneously. A real-time model of the proposed 23-level H-PUC converter and its suggested FCS-MPC are developed and implemented in OPAL-RT OP4510 platform to evaluate and validate the feasibility of the proposed H-PUC in grid-connected operation mode. The provided real-time implementation results verify and demonstrate the performance and viability of the proposed 23-level H-PUC and its associated FCS-MPC to provide low THD 23-level output voltage and all three capacitors voltages balancing.